2020
DOI: 10.1186/s12905-020-01009-2
|View full text |Cite
|
Sign up to set email alerts
|

Continuum of sexual and gender-based violence risks among Syrian refugee women and girls in Lebanon

Abstract: Background: A myriad of factors including socioeconomic hardships impact refugees, with females being additionally exposed to various forms of sexual and gender-based violence (SGBV). The aim of this qualitative analysis was to understand and to provide new insight into the experiences of SGBV among Syrian refugee women and girls in Lebanon. Methods: The data are gained from a larger mixed-methods study, investigating the experiences of Syrian refugee girls in Lebanon, using an iPad and the data collection too… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 40 publications
0
18
0
1
Order By: Relevance
“…This confusion is possibly due to the marginalization of the process of puberty [ 44 ] , where females stated they had limited knowledge and comprehension about menstruation before reaching menarche [ 45 ]. This shows the lack of awareness of parents, particularly the mothers who were the most common source of knowledge in several studies regarding teaching their daughters about menstruation [ 45 48 ]. The figures in the aforementioned studies were similar to those presented in this study.…”
Section: Discussionmentioning
confidence: 99%
“…This confusion is possibly due to the marginalization of the process of puberty [ 44 ] , where females stated they had limited knowledge and comprehension about menstruation before reaching menarche [ 45 ]. This shows the lack of awareness of parents, particularly the mothers who were the most common source of knowledge in several studies regarding teaching their daughters about menstruation [ 45 48 ]. The figures in the aforementioned studies were similar to those presented in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The ASIST-GBV, a form of anonymous self-administered GBV survey, has been used to screen for GBV within humanitarian settings [ 31 ]. The study by Roupetz, Garbern [ 32 ] elaborated on their measure of using a SenseMaker survey – a self-administrated survey that does not ask explicit questions on GBV but instead allow for narratives to allow GBV experiences to become apparent. These methods of data collection have been considered to be largely successful thus far by the cited studies.…”
Section: Overview Of Studiesmentioning
confidence: 99%
“…Keygnaert et a.l [ 37 ] found that within the context of asylum-seeker arrivals into EU reception centers, the most common perpetrators of GBV are (ex-)partners and asylum professionals. 3 Delving more into IPV, female irregular migrants, asylum-seekers, and rural-to-urban households seem particularly vulnerable to IPV due to the stresses induced by migration on the perpetrators [ 32 , 53 56 ].…”
Section: Power Imbalance As a Primary Risk-factormentioning
confidence: 99%
“…Interpersonal risk factors include relationships with others that can increase the odds of a mental health conditions. Existing literature highlight refugee women to be vulnerable to intimate partner violence (IPV) [ 21 , 25 ], making IPV a serious health and human rights problem at the interpersonal level. IPV is estimated to affect 30% of women during their lifetime [ 26 ], and is associated with increased risk of mental health conditions [ 27 ].…”
Section: Introductionmentioning
confidence: 99%